Modeling Wound-Closure Response Over Time in Douglas-Fir Trees. Issue 2 (2nd November 2018) - Jones, Dryw A; Harrington, Constance A; Marshall, David
Abstract: Wound closure is an important component of tree recovery from bole damage. Damage to young Douglas-fir ( Pseudotsuga menziesii [Mirb.] Franco) stands in the precommercial and commercial stages is common, yet few studies have looked at how trees at these stages of stand development respond to common forms of damage. Using data from a 10-year study of artificially damaged Douglas-fir trees, we found reduced potential for relative wound closure with increasing initial tree bole diameter, and increasing initial relative bole area damaged. Wound-closure rates increased for longer periods of time in more vigorous trees, trees on better-quality sites, and trees with intact live crowns. Wound-closure rates were reduced for trees with more relative bole damage, smaller live crown cross-sections, slower relative diameter growth, and more crown competition. Trees with low levels of bole damage relative to lower bole surface area produced more callus tissue than was necessary to cover the original wound, suggesting that long-term tree stability should recover for low levels of bole damage.